Enlargement of communities in the context of administrative territorial reforms - Otaryan, Mher (Bulletin of Yerevan University G: Economics, 2024)
In this article we referred to the process of enlargement in RA communities in the context of administrative and territorial reforms. Administrative territorial reforms in the regions of the Republic of Armenia started in 2015-2017 and as a result of the implemented three-phase community enlargement process in 2018. As of now, the number of communities in the Republic of Armenia decreased from 915 to 502, with 52 clusters of multi-residential communities. Referring to the changes in the management system of the enlarged communities, we noted that as a result of the enlargement, first of all, in the communities of Armenia, there was a redistribution of the posts of the staff of the communities, as a result of which the administrative and repetitive posts of the communities were significantly reduced. We also studied the revenues and expenses of the budgets of the enlarged municipalities and showed that as a result of the enlargement process, cost planning and an increase in municipal incomes took place. Thus, the enlargement of communities has generally had a positive effect and has the potential and strength to develop further. In this way, communities have become more self-financing and the level of decentralization has increased even more. Key words: RA government, community, NFPO, enlargement of communities, local government, position, administrative unit, budget, income, expenses.